2017
DOI: 10.1139/cjpp-2016-0367
|View full text |Cite
|
Sign up to set email alerts
|

Icariin improves eNOS/NO pathway to prohibit the atherogenesis of apolipoprotein E-null mice

Abstract: These findings suggested icariin could improve eNOS / NO-pathway to prohibit the atherogenesis of apolipoprotein E null mice by restraining oxidative stress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
15
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 27 publications
2
15
0
Order By: Relevance
“…Previous studies have suggested that Icariin attenuated the development of atherosclerosis in several animal models, including ApoE -/- mice ( Xiao et al, 2015 , 2017 ; Wang et al, 2016 ), rats ( Hu et al, 2015b ), and rabbits ( Zhang et al, 2013 ). The atheroprotective mechanisms of Icariin are exerted through anti-oxidative, anti-inflammatory, anti-thrombotic, and lipid-modulatory effects.…”
Section: Anti-atherosclerotic Effects Of Icariinmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have suggested that Icariin attenuated the development of atherosclerosis in several animal models, including ApoE -/- mice ( Xiao et al, 2015 , 2017 ; Wang et al, 2016 ), rats ( Hu et al, 2015b ), and rabbits ( Zhang et al, 2013 ). The atheroprotective mechanisms of Icariin are exerted through anti-oxidative, anti-inflammatory, anti-thrombotic, and lipid-modulatory effects.…”
Section: Anti-atherosclerotic Effects Of Icariinmentioning
confidence: 99%
“…In terms of the important role of SIRT6 in regulating endothelial dysfunction and atherosclerosis ( Liu et al, 2016 ; Xu et al, 2016a , c ; Zhang et al, 2016 ), Icariin has recently been reported as a SIRT6 pharmacological activator in vitro and in vivo ( Chen et al, 2015 ), pinpointing the potential contribution of SIRT6 activation to the atheroprotective effects of Icarrin. The endothelial protective effects of Icariin contributed to upregulation of eNOS-dependent NO production in ApoE -/- mice fed a high fat diet ( Xiao et al, 2017 ).…”
Section: Anti-atherosclerotic Effects Of Icariinmentioning
confidence: 99%
“…Ox‐LDL, as an important trigger of AS, has been reported to induce endothelial dysfunction via reducing eNOS activity and NO level . A previous study demonstrated that icariin could prohibit atherogenesis by increasing NO concentration and eNOS expression . In this study, we further investigated the role of GA fragmentation in ox‐LDL‐induced endothelial dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…24,26 A previous study demonstrated that icariin could prohibit atherogenesis by increasing NO concentration and eNOS expression. 27 In this study, we further investigated the role of GA fragmentation in ox-LDL-induced endothelial dysfunction. To mitigate GA fragmentation, HUVECs were transfected with GRASP65 plasmid.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a reduction in the bioavailability of vascular NO will precipitate atherosclerosis process. Functional studies were used to validate these protective effects by using gene disrupted mice that confirmed the role of NO in limiting the vascular atherosclerotic damage 14,47,48 . However, the causal relation between eNOS gene polymorphisms and CAD can't be simply confirmed in human because the aetiology for CAD is stratified by other risk factors such as obesity, smoking, hypertension, diabetes and lifestyle 49,50 .…”
Section: ) Cad Control ---------------------------------------------mentioning
confidence: 99%